PENGARUH MEDIA SOSIAL TERHADAP PENGALAMAN NILAI-NILAI PANCASILA DI KALANGAN GENERASI Z - Pipin Windriani; Farha Maulida; Shofia Kamila; Zaenul Slam (Didaktik : Jurnal Ilmiah PGSD STKIP Subang, 2026)
Pancasila, which is the foundation of the state and the ideology of the Indonesian nation, plays an important role in shaping moral and ethical values that serve as a guide for life in society. Amid the rapid flow of globalization and advances in digital technology, Generation Z, as today's young generation, faces various foreign cultural challenges that trigger a decline in social awareness, individualism, and even moral decay. This study aims to analyze the positive and negative impacts on social media users regarding the practice of Pancasila values among Generation Z, identify the factors causing moral decay, and formulate adaptive revitalization strategies in the digital era. The data analysis technique used in this study is a qualitative descriptive analysis with a literature study approach sourced from books, scientific journals, and related articles. The discussion results show that social media has a positive impact by making collaborative communication easier in spreading the values of Pancasila, but it also brings negative effects like addiction, mental health issues, and the spread of hoaxes, which pose a threat of radicalization that clouds understanding of national ideology. Therefore, strategies are needed to revitalize Pancasila values through cross-sector collaboration, innovative Citizenship Education learning based on local wisdom, and creative use of digital platforms to reinforce morality, ethics, and the sense of nationalism among Generation Z.